The harmful chemistry behind "krokodil": Street-like synthesis and product analysis - Alves, Emanuele Amorim; Soares, José Xavier; Afonso, Carlos Manuel; Grund, Jean-Paul C; Agonia, Ana Sofia; Cravo, Sara Manuela; Netto, Annibal Duarte Pereira; Carvalho, Félix; Dinis-Oliveira, Ricardo Jorge (Forensic science international, 2015)
"Krokodil" is the street name for a drug, which has been attracting media and researchers attention due to its increasing spread and extreme toxicity. "Krokodil" is a homemade injectable mixture being used as a cheap substitute for heroin. Its use begun in Russia and Ukraine, but it is being spread throughout other countries. The starting materials for "krokodil" synthesis are tablets containing codeine, caustic soda, gasoline, hydrochloric acid, iodine from disinfectants and red phosphorus from matchboxes, all of which are easily available in a retail market or drugstores. The resulting product is a light brown liquid that is injected without previous purification. Herein, we aimed to understand the chemistry behind "krokodil" synthesis by mimicking the steps followed by people who use this drug. The successful synthesis was assessed by the presence of desomorphine and other two morphinans. An analytical gas chromatography-electron impact/mass spectrometry (GC-EI/MS) methodology for quantification of desomorphine and codeine was also developed and validated. The methodologies presented herein provide a representative synthesis of "krokodil" street samples and the application of an effective analytical methodology for desomorphine quantification, which was the major morphinan found. Further studies are required in order to find other hypothetical by-products in "krokodil" since these may help to explain signs and symptoms presented by abusers.
Keywords: zakázané drogy; Codeine; Limit of Detection; limita detekce; Chromatography, Liquid; Humans; kodein; Desomorphine; GC-EI/MS analysis; lidé; Opioid abuse; Substance Abuse, Intravenous; soudní toxikologie; plynová chromatografie s hmotnostně spektrometrickou detekcí; chromatografie kapalinová; Forensic Toxicology; Gas Chromatography-Mass Spectrometry; intravenózní abúzus drog; Illicit Drugs; “Krokodil” synthesis